PENGARUH HARGA, LOKASI, DAN FASILITAS TERHADAP LOYALITAS KONSUMEN MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING DI BEACH FOREST KLATAKAN SITUBONDO - Maulidayanti, Elsa Bela; Wahyuni, Ika; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The results of direct effect hypothesis testing, using Smart PLS 3.2.8 software, show that Price does not have a significant effect on Consumer Satisfaction; Location has a significant positive effect on Consumer Satisfaction; Facilities have a positive but not significant effect on Consumer Satisfaction; Price have a positive but not significant effect on Consumer Loyalty; Location has a negative but not significant effect on Consumer Loyalty; Facilities have a positive but not significant effect on Consumer Loyalty; and Consumer Satisfaction has a significant positive effect on Consumer Loyalty. The results of indirect effect hypothesis testing show that Price has a positive but not significant effect on Consumer Loyalty through Consumer Satisfaction; Location has a significant positive effect on Consumer Loyalty through Consumer Satisfaction; and Facilities have a positive but not significant effect on Consumer Loyalty through Consumer Satisfaction.